Kilka uwag o doktrynalnych uwarunkowaniach aktualnego kryzysu ustrojowo-politycznego w Polsce - Ciapała, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Author refers to Arthur Preisner's article, in which subject and need of the direct application of Polish Constitution was indicated. As we all know, some political and legal facts caused, the situation in contemporary Poland is difficult and complex. They are just mentioned in the article. Nevertheless, the constitutional crisis is generally described. The main and the most significant part of the text deals with the doctrinals points of views presented by Carl Schmitt and Hans Kelsen in the last century. They may be regarded as the lawyers who - among the theory and philosophy of law representatives - influenced the political scene and the positions of doctrine very significantly. They are of great importance from Polish "internal and domestic" point of view and situation, because their conceptions seemed to be reflected in some motives and justifications within the political area. There is no one conclusion after the analyses presented in the article. Maybe one of conclusions is not to be attached and not to pay great attention or importance to one particular doctrine or opinion formulated in the past time.
Keywords: the influence of legal doctrine to the contemporary policy; critical judgments of Carl Schmitt positions; Polish constitutional and political crisis'; some problem with Hans Kelsen theory in modern times